2021
DOI: 10.1097/gox.0000000000003422
|View full text |Cite
|
Sign up to set email alerts
|

Legislation, Market Size, and Access to Gender-affirming Genital Surgery in the United States

Abstract: Background: The value of gender-affirming genital surgery (GAGS) has been established for certain transgender or gender non-conforming patients. This study aimed to determine the availability of GAGS by state and region in the United States, and to query possible associations of access to care with healthcare legislation and local market size. Methods: This was a cross-sectional study reporting on the distribution of hospitals and private practices offering GAGS in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Waiting lists may serve as an index of demand and operational capacity but may also reflect the impact of other factors such as financial constraints in a practice or the coverage of procedures by insurance. Accordingly, it may be productive to compare waiting lists discovered in this study with those found in analyses of other types of specialized health care provision 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waiting lists may serve as an index of demand and operational capacity but may also reflect the impact of other factors such as financial constraints in a practice or the coverage of procedures by insurance. Accordingly, it may be productive to compare waiting lists discovered in this study with those found in analyses of other types of specialized health care provision 29 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that most physicians offering GABS are geographically concentrated in metropolitan areas, with greater than 55% practicing in Northeastern and West Coast states 28 . In addition, 47% of American states did not have a physician practice offering GABS 29 . A future of accessible health care for transgender patients would ideally include greater national distribution of health care practices that serve their medical needs without financial barriers.…”
Section: Discussionmentioning
confidence: 99%
“…A small increase in the utility of gender-affirming care among self-pay patients in inclusion states was also noted. This may be due to cohort effects, arising from the culturally liberal nature of Northeastern states, better care access in those states, 13 or a response to the nationwide loosening of federal restrictions on gender-affirming care.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] As the stigma associated with such procedures has started to recede, the field began a rapid growth with the current workforce insufficient to meet demand. [5][6][7] With this growth, a paradigm shift will be critical to preserving the quality of care. This is in part brought on by the rising popularity of procedures far more rarely attempted in previous decades.…”
Section: Introductionmentioning
confidence: 99%